2014
DOI: 10.3109/09638288.2014.932442
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic score for work disability in Romanian patients with ankylosing spondylitis

Abstract: Work disability is an important outcome in AS, determined by numerous variables but highly dependent on the national characteristics of economy, social security and healthcare system. The prognostic score for work disability in AS not only contains medical but also socio-demographic and work-related factors and is expected to be a useful tool for specialists to guide the tertiary prevention-oriented rehabilitation measures. Our study suggests the prognostic score to be comprehensive, useful and a reliable meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Our study showed that older people did not frequently resume their professional activity and applied for other forms of social benefits. Age has been identified in many studies as a strong predictor for employee absenteeism [ 17 , 30 32 ]. However, the relationship is not analysed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that older people did not frequently resume their professional activity and applied for other forms of social benefits. Age has been identified in many studies as a strong predictor for employee absenteeism [ 17 , 30 32 ]. However, the relationship is not analysed in detail.…”
Section: Discussionmentioning
confidence: 99%